Storage volumestorage volumestorage volumeRainwater Harvesting System as an Alternative to Overcoming Drought in Safira Garden Housing District, Kec. Kaliwates District. Jember - Lailyasari , Fahira Dwi; Rizal , Nanang Saiful; Galuh , Senki Desta (Universitas Muhammadiyah Jember, 2023)
Rainfall is the most important component in a rainwater harvesting system. This rainwater harvesting system integrated with infiltration wells is an effort to avoid the problem of drought. One of the reasons why rainwater harvesting systems are important for water conservation is that increasing water demand causes an increase in groundwater extraction, thereby reducing groundwater reserves. Data collection was obtained through direct surveys to research locations and related agencies. Next, technical planning or building design for Rainwater Harvesting with infiltration wells is carried out, including buildings for storing or harvesting rainwater (rainwater harvesting) and rainwater infiltration into infiltration wells in each house. This research analyzes the implementation of a rainwater harvesting system using infiltration wells, with the aim of finding out the volume of rainwater that can be accommodated in the rainwater harvesting system and the costs required in the rainwater harvesting system. The river basin (DAS) in the Safira Garden area, Kaliwates District, Jember Regency has an area of 16 hectares or 0.16 km 2 . The results of the research show that the volume of rainwater that can be collected in the rainwater harvesting system at Safira Garden Housing, namely that which is collected in the absorption wells throughout the house is 66.04 m 3 and the total volume in the storage pond is 5303.36 m 3 . Funding for the rainwater harvesting system is estimated at Rp. 9,253,000.00 for rainwater utilization facilities with infiltration wells and rainwater storage areas equipped with water pumps to provide upward pressure and water filters to filter rainwater before it is used for domestic needs.